2023
DOI: 10.1002/anie.202305121
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear Gold‐Catalyzed 1,2‐Difunctionalization of Alkenes

Abstract: Activated alkyl halides have been extensively explored to generate alkyl radicals with Ru‐ and Ir‐ photocatalysts for 1,2‐difunctionalization of alkenes, but unactivated alkyl bromides remain challenging substrates due to their strong reduction potential. Here we report a three‐component 1,2‐difunctionalization reaction of alkenes, unactivated alkyl bromides and nucleophiles (e.g., amines and indoles) using a trinuclear gold catalyst [Au3(tppm)2](OTf)3. It can achieve the 1,2‐aminoalkylation and 1,2‐alkylaryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As a prototype example of the dinuclear gold(I) photocatalysts, [Au 2 (μ-dppm) 2 ] 2 + (dppm =bis(diphenylphosphino)methane) has been extensively utilized to achieve various photo-induced transformation, such as CÀ X bond cleavage, CÀ C, CÀ N crossing-coupling and formal radical-radical coupling. [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Detailed reviews of most of these results can be found elsewhere, [6][7][8]29] and thus, will not be reiterated here. This concept focuses on contributions toward the understanding of the ISET mechanism in polynuclear gold photoredox reactions.…”
Section: Iset In Polynuclear Gold Photocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a prototype example of the dinuclear gold(I) photocatalysts, [Au 2 (μ-dppm) 2 ] 2 + (dppm =bis(diphenylphosphino)methane) has been extensively utilized to achieve various photo-induced transformation, such as CÀ X bond cleavage, CÀ C, CÀ N crossing-coupling and formal radical-radical coupling. [7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Detailed reviews of most of these results can be found elsewhere, [6][7][8]29] and thus, will not be reiterated here. This concept focuses on contributions toward the understanding of the ISET mechanism in polynuclear gold photoredox reactions.…”
Section: Iset In Polynuclear Gold Photocatalysismentioning
confidence: 99%
“…By expanding the concept of ISET of polynuclear gold complexes, Xie and coworkers recently reported a three-component 1,2-difunctionalization reaction of alkenes, unactivated alkyl bromides and nucleophiles (such as amines and indoles), using trinuclear gold catalyst [Au 3 (tppm) 2 ](OTf) 3 (Scheme 6). [28] The approach exhibits broad substrate applicability and can activate inert primary, secondary, and tertiary bromides to generate alkyl radicals. In-depth investigations into the reaction mechanism were also conducted.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Radical cascade reactions have proven to be an important and effective tool in modern organic synthesis in the past decades . In recent years, visible-light photoredox catalysis as an attractive strategy to assemble diverse carbocyclic and heterocyclic skeletons has become one of the most exciting developments in the field of organic synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…1). 7–10 Therefore, many strategies for the synthesis of 1-pyrrolines have been developed by synthetic chemists, and the common methods include the intramolecular cyclization of bifunctional compounds and intermolecular multicomponent cycloaddition 11–14 and [3 + 2] cycloaddition of 1,3-dipoles and alkenes or cyclopropanes (the Huisgen cycloaddition reaction). 15–19 The intramolecular Schmidt rearrangement of alkyl azides provides an alternative route to 1-pyrrolines, 20 although only moderate yields were observed in early studies.…”
Section: Introductionmentioning
confidence: 99%